2008
DOI: 10.1016/j.janxdis.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatment of comorbid asthma and panic disorder: A pilot study

Abstract: We evaluated two protocols for treating adults with comorbid asthma and panic disorder. The protocols included elements of Barlow's panic control therapy and elements of Barlow's "panic control therapy" and several asthma education programs, as well as modules designed to teach participants how to differentiate asthma and panic symptoms, and how to apply specific home management strategies for each. Fifty percent of subjects dropped out of a 14-session protocol by the eighth session; however, 83% of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 59 publications
0
46
0
Order By: Relevance
“…Psychological interventions in patients with asthma, particularly children, remain uncertain, their effects being quite variable [138][139][140][141]. Yorke et al performed a systematic review on the efficacy of psychological interventions in asthma [142].…”
Section: Psychopathologiesmentioning
confidence: 99%
“…Psychological interventions in patients with asthma, particularly children, remain uncertain, their effects being quite variable [138][139][140][141]. Yorke et al performed a systematic review on the efficacy of psychological interventions in asthma [142].…”
Section: Psychopathologiesmentioning
confidence: 99%
“…Although studies have indicated that treatment of panic disorders can improve asthma outcomes, the authors of a Cochrane meta-analysis on the role of psychological interventions for children with asthma were unable to draw firm conclusions about the efficacy of this approach [70][71][72][73]. Studies reporting positive effects were usually conducted by specialists treating well-defined psychopathological comorbidities, whereas studies of psychoeducational interventions carried out by nonspecialists seemed less effective.…”
Section: Psychopathologiesmentioning
confidence: 99%
“…However, there were some suggestions of improved asthma outcomes associated with a number of interventions targeted on reducing anxiety and depression such as relaxation therapy, CBT, and biofeedback. Recent pilot studies in patients with co-morbid anxiety and depression have reported improved asthma outcomes in patients undergoing panic control programmes 53 or treatment with antidepressant medication. 54 Both these studies were small and preliminary so further research is needed.…”
Section: Can Treatment Of Anxiety and Depression Improve Asthma Control?mentioning
confidence: 99%